Solar disinfection of water for diarrhoeal prevention in southern India. Issue 2 (10th January 2006) - Rose, A; Roy, S; Abraham, V; Holmgren, G; George, K; Balraj, V; Abraham, S; Muliyil, J; Joseph, A; Kang, G
Abstract : Aims: To evaluate the efficacy and acceptability of solar irradiation in the prevention of diarrhoeal morbidity in children under 5 years of age, in an urban slum in Vellore, Tamil Nadu. Methods: A total of 100 children were assigned to receive drinking water that had been subjected to solar disinfection in polyethylene terephthalate bottles. One hundred age and sex matched controls were also selected. Both groups were followed by weekly home visits for a period of six months for any diarrhoeal morbidity. At the end of the follow up period, the acceptability of the intervention was assessed by interviews, questionnaires, and focus group discussions. Results: There was significant reduction in the incidence, duration, and severity of diarrhoea in children receiving solar disinfected water, despite 86% of the children drinking water other than that treated by the intervention. The incidence of diarrhoea in the intervention group was 1.7 per child-year, and among controls 2.7 per child-year, with an incidence rate ratio of 0.64 (95% CI −0.48 to 0.86). The risk of diarrhoea was reduced by 40% by using solar disinfection. In qualitative evaluation of acceptability, most women felt that solar disinfection was a feasible and sustainable method of disinfecting water. Conclusions: Solar disinfection of water is an inexpensive, effective, and acceptable method of increasing water safety in a resource limited environment, and can significantly decrease diarrhoeal morbidity in children.